Strategies for minimizing the influence of the use of BYOD and Cloud in organizations: 4CM Model - Moreira, Fernando (2018)
In the last decade, companies have become tend virtualized thanks to the use of outsourcing, the workforce has become more distributed, workplaces are increasingly distributed and outsourced and increasingly digital employees, with the philosophy of work anytime and anywhere. This development has, and has had a very big impact on mobile platforms and infrastructure, on the one hand, the adoption of the BYOD concept and the use of mobile devices and on the other hand, through the use of cloud computing will have profound implications in the way the technologies are and will be used as well as on the interaction between individuals and these technologies. By applying for a questionnaire and subsequent analysis showed that organizations have a lack of understanding, almost complete, the implications and consequences of using mobile devices and the cloud in organizations. A result of the Focus Group performed we propose the 4CM model.